Idealização e (des)valorização da profissão docente na visão de professores do Ensino Público - Zacharias, Larissa Rodrigues (Universidade Federal de São Carlos, 2023)
Idealizations are forms of exaltation of unknown situations, forming impressions that often do not match reality. In the context of teaching performance, these idealizations can directly or indirectly affect the work of the teacher, causing even more devaluation of the teaching profession, especially when these idealized situations are romanticized. These idealizations can either be imposed by the teachers themselves during graduation, or by society and the system. The objective of this monograph, then, is oriented towards understanding elements of idealization and (devaluation) of the teaching profession in the view of public school teachers. This research is qualitative in nature, using semi-structured interviews conducted with teachers, using discourse analysis for the data. The results obtained from the interviews show that the idealizations present a weight in the teaching career itself, especially with the devaluation of education and the vision of these teachers in society. It is necessary to understand the elements from which these idealizations arise and how the true perceptions of the teaching career can be transmitted to society, thus preventing teacher devaluation.
Idelization and (de)valorization of the teaching profession in the view of public school teachers
Keywords: Formação docente; Idealização; Desvalorização; Aparência e essência; Teacher training; Idealization; Devaluation; Appearance and essence; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO